Drug use stigma, accidental pet poisonings, and veterinary care: results from a survey of pet owners in Vancouver, British Columbia - Chambers, Chloe; Ly, Lexis H.; Protopopova, Alexandra (Frontiers in Veterinary Science, 2025)
IntroductionThe effect of drug use on physical health, mental wellbeing, and quality of life can extend to family members, including children, and even companion animals. People who use drugs, a medically vulnerable population, face stigma and shaming when accessing healthcare services that engender mistrust and hinder future access. Yet, in an emergency where a pet has accidentally ingested drugs, there is no research on whether this stigma may prevent owners from seeking veterinary help. The objectives of this study were to describe actions taken by pet owners after accidental pet drug poisonings in Vancouver, British Columbia and understand how drug use-related stigma is associated with owners’ decision to seek veterinary care.MethodsWe surveyed two populations of pet owners, a general population recruited online (n = 82) and a sample recruited in-person at two outreach services that assist low-income pet owners in the Downtown Eastside of Vancouver (n = 32). Participants who had not experienced a pet poisoning were asked about their actions and attitudes in a hypothetical drug poisoning event.ResultsWithin the general population sample, 64 (78%) responded based on a hypothetical scenario, and in this group, the concern that a veterinarian might remove their animal was associated with higher self-reported discrimination in three domains: general discrimination, discrimination accessing non-health services, and discrimination accessing health-related services. A higher perceived experience of discrimination within each category was also associated with a greater concern that veterinary staff might report them to the authorities or social services, as well as an increased expectation of hiding information from a veterinarian, including information about what drug the animal ingested and how the animal was exposed. Those who had experienced a poisoning emergency were asked about their actions and encounters in the most recent poisoning. More than half sought veterinary assistance. Among those that did not, some reasons owners avoided veterinary care included confidence in their ability to treat the animal at home (n = 5), or fear of discrimination (n = 1) or punishment (n = 1).DiscussionOur findings suggest that drug use-related stigma may contribute to a hesitancy to seek veterinary care or fully disclose information in an accidental pet poisoning.